2014
DOI: 10.1007/s00702-014-1277-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of single cell activity in the globus pallidus internus of patients with dystonia or Tourette syndrome

Abstract: Altered processing in the basal ganglia has been described both in dystonia and Tourette's syndrome (TS). Deep brain stimulation (DBS) of the globus pallidus internus (GPi) has become a recognized treatment for dystonia and has been used successfully to alleviate tics in TS. This study evaluates possible differences of GPi linear and nonlinear neuronal discharge characteristics between patients with dystonia and TS. Nine patients with primary dystonia and six patients with TS were studied during functional ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 73 publications
5
22
1
1
Order By: Relevance
“…Our results are in line with both studies, which found a rate decrease in the GPi compared to rates recorded in PD patients or normal nonhuman primates . Interestingly, the reduced firing rates that we observed in the GPe are comparable to those previously observed in awake patients suffering from other hyperkinetic disorders, such as dystonia and hemiballismus …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with both studies, which found a rate decrease in the GPi compared to rates recorded in PD patients or normal nonhuman primates . Interestingly, the reduced firing rates that we observed in the GPe are comparable to those previously observed in awake patients suffering from other hyperkinetic disorders, such as dystonia and hemiballismus …”
Section: Discussionsupporting
confidence: 93%
“…No studies of the associative/limbic (anterior) GPi or any part of GPe tonic activity during TS have been previously conducted. Tonic activity changes in the motor (posterior) GPi during TS have been partially addressed in previous studies of anesthetized and awake patients undergoing a mapping procedure. Our results are in line with both studies, which found a rate decrease in the GPi compared to rates recorded in PD patients or normal nonhuman primates .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of theta oscillations in patients with TS has previously been reported in case series for the internal pallidum (with n = 1–7 patients; all recorded intraoperatively and thalamic CM/Voi region (with n = 1–7 patients; however, a clear association with TS symptoms has only been shown in few individuals and comparison to healthy controls is obviated by the invasive approach. Here, we use simultaneous signal acquisition from both the pallidal and thalamic target to demonstrate that both structures are functionally coupled in this frequency range.…”
Section: Discussionmentioning
confidence: 78%
“…Electrodes were implanted with computed tomography (CT)‐stereotactic surgery supported by preoperative magnetic resonance imaging under general anesthesia. Microelectrode recordings helped further refinement of the target, by allowing the identification of residual intranuclear spiking activity and the presence of pallidal border cells that are unaffected by general anesthesia . Preliminary target coordinates for the posteroventral lateral GPi were 20 to 22mm lateral to and 4mm below the intercommissural line, and 2 to 3mm anterior to the midcommissural point; for the CM/Voi, 5 to 6mm lateral to and at the level of the intercommissural line and 3 to 4mm posterior to the midcommissural point (with a slightly angled trajectory) .…”
Section: Methodsmentioning
confidence: 99%
“…During surgery, neuronal activity of single units can be examined with microelectrode recording (Shields et al, 2008;Zhuang et al, 2009;Alam et al, 2014). After surgery, when the leads of the implanted probe are externalized and before implantation of the pulse generator, local field potentials (LFPs) of neuronal assemblies can be detected (Marceglia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%